CONSULATATION - ACTIVE FORM OF HUMAN ANATOMY STUDY - Попадинець, О.Г. (World of Medicine and Biology, 2014)
At the chair of Human Anatomy the approaches to organizational-methodical methods of the learning process, using teaching methods, whose ultimate goal is to form a stable conscious motivation to study not only the curriculum material, but also additional one, to instill an interest in anatomy and medicine in general, were implemented. Such form minimizes the possibility of a positive assessment of students’ knowledge who are not systematically used to study, but from time to time, and increases the extent of their responsibility. Work in this mode is difficult enough and needs a lot of effort, but the results are encouraging.
Keywords: Human Anatomy; organizational-methodical support